FATIGUE AND WORK SATISFACTION OF EMERGENCY NURSES IN BANDUNG, WEST JAVA, INDONESIA - Wiwin Yudiah; Kurniawan Yudianto; Ayu Prawesti (Belitung Raya Foundation, Indonesia, 2018)
Background: Emergency nurses are required to always carry out their roles in a variety of situations and conditions. Nursing services in the emergency unit must be done quickly and accurately. Data showed that the number of patient visits in the Emergency Unit of Hasan Sadikin Hospital in August 2017 was 3,059 (73% of patients with category III) with an average visit of 99 people per day. This causes overcrowding in the emergency unit, which lead to fatigue and influence work satisfaction. Aim: The aim of this study was to determine fatigue and job satisfaction of emergency nurses in Hasan Sadikin Hospital in Bandung, West Java, Indonesia. Methods: This was a quantitative descriptive study, which involved 55 respondents. Fatigue was measured using Individual Strength Checklist Instrument of 20-self-reported questionnaire (CIS20R), and job satisfaction was measured using McCloskey / Mueller Satisfaction Scale (MMSS). Results: The mean value of work fatigue was 3.4 with the highest value at the sub variable of physical activity. In general, the mean value of nurse work satisfaction was 2.66. Conclusion: Emergency nurses in the emergency unit of Hasan Sadikin hospital has high level of fatigue and low work satisfaction. The hospital management is suggested to provide better work schedule for better interaction among nurses, provide opportunities for all staff to be involved in research or other scientific work, and schedule family gatherings regularly to improve togetherness between staff and their families.